Pengenalan ChatGPT dalam Proses Pembelajaran di SMK Brahari untuk Mendukung Pembelajaran Mandiri dan Efektif - Nawangsih, Ismasari; Widodo, Edy; Budiarto, Eko; Majid, Annisa Maulana; Purnamasari, Pupung (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research aims to introduce the use of ChatGPT in the learning process at Brahari Vocational School as an effort to support independent and effective learning for students. In today's digital era, artificial intelligence technology, such as ChatGPT, can be a very useful tool in improving students' learning experiences, especially at the secondary education level. ChatGPT allows direct interaction that can help students understand material, solve problems, and answer various questions in real-time. This research examines the implementation of ChatGPT in various subjects at Brahari Vocational School, with a focus on how this technology supports students in independent learning outside formal lesson hours. The method used is a qualitative approach through interviews with teachers and students, as well as observations of the use of ChatGPT in learning activities. The research results show that using ChatGPT can increase student motivation, make it easier to understand difficult material, and accelerate the achievement of more effective learning outcomes. In addition, students also show an increase in the ability to search for information independently and develop critical skills. This research concludes that ChatGPT has great potential to support more flexible and sustainable learning at Brahari Vocational School, as well as contributing to more effective independent learning.